2014
DOI: 10.1371/journal.pone.0107867
|View full text |Cite
|
Sign up to set email alerts
|

A New Mouse Allele of Glutamate Receptor Delta 2 with Cerebellar Atrophy and Progressive Ataxia

Abstract: Spinocerebellar degenerations (SCDs) are a large class of sporadic or hereditary neurodegenerative disorders characterized by progressive motion defects and degenerative changes in the cerebellum and other parts of the CNS. Here we report the identification and establishment from a C57BL/6J mouse colony of a novel mouse line developing spontaneous progressive ataxia, which we refer to as ts3. Frequency of the phenotypic expression was consistent with an autosomal recessive Mendelian trait of inheritance, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…Besides, it is reported that duplications of SLC1A3 was associated with ADHD, and behavioral problems resembling ADHD are observed, which is in line with the glial glutamate transporter role of SLC1A3 . These studies support the involvement of the 5p13 region in ADHD, the single region of overlap in a pooled analysis of US and Dutch genome‐wide linkage data . However, Nancy et al failed to replicate the association between SLC1A3 (rs3776581, rs2269272 and rs2032893) and ADHD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it is reported that duplications of SLC1A3 was associated with ADHD, and behavioral problems resembling ADHD are observed, which is in line with the glial glutamate transporter role of SLC1A3 . These studies support the involvement of the 5p13 region in ADHD, the single region of overlap in a pooled analysis of US and Dutch genome‐wide linkage data . However, Nancy et al failed to replicate the association between SLC1A3 (rs3776581, rs2269272 and rs2032893) and ADHD .…”
Section: Discussionmentioning
confidence: 99%
“…33 These studies support the involvement of the 5p13 region in ADHD, the single region of overlap in a pooled analysis of US and Dutch genome-wide linkage data. 34 However, Nancy et al failed to…”
Section: Discussionmentioning
confidence: 99%
“…Using the Analyze Skeleton plugin of Image J software, spines densities were analyzed in random selected distal branches between 10 and 20 μm in length. Spine morphology analysis was performed as previously described with some changes (Miyoshi et al, 2014) (See Supplemental Information). …”
Section: Methodsmentioning
confidence: 99%
“…Notably, GluD2 is associated with autism spectrum disorder, schizophrenia, cerebellar ataxia, intellectual disability, attention deficit hyperactivity disorder, and motor and cognitive deficit disorders (Kashiwabuchi et al, 1995;Kondo et al, 2005;Katoh et al, 2005;Utine et al, 2013;Miyoshi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%